High-Speed and High-Resolution Demodulation System for the Hybrid WDM/FDM Based Fiber Microstructure Sensing Network - Jianwei Cheng; Qizhen Sun; Fan Ai; Yiyang Luo; Wei Zhang; Xiaolei Li; Deming Liu (IEEE Photonics Journal)
A hybrid wavelength-division multiplexing/frequency-division multiplexing (WDM/FDM) based optical fiber microstructure sensing network with large capacity, high resolution, and high-speed response is proposed and demonstrated. The sensing network is composed of a demodulation system and a fiber microstructure sensor array distributed along a single fiber. Parallel processing technology is utilized for investigating the envelope peak and the fringe peak of the spectrum simultaneously, which can be used to distinguish large-scale temperature shifts quickly. In combination with a high-speed tunable Fabry–Perot filter, the sensor array can be quickly demodulated with the speed up to 500 Hz as well as the wavelength resolution less than 3 pm. In a proof-of-concept experiment, an array composed of 16 sensors through four WDM and four FDM is employed for temperature measurement, demonstrating a temperature resolution less than ±0.3 °C, and a vibration experiment verified 500 Hz demodulation speed capacity. Compared with traditional demodulation schemes, the proposed demodulation system is suitable for large capacity networks and dynamic sensing applications.